CHINA’S DIGITAL SILK ROAD AND CYBER DIPLOMACY: BUILDING INFLUENCE IN THE CYBER SPHERE (Contemporary Journal of Social Science Review, 2025)
China's Digital Silk Road (DSR) and cyber diplomacy are central to China's broader Belt and Road Initiative (BRI), aimed at enhancing global connectivity and expanding its influence. This study explores the strategic role of the DSR in the cyber sphere, focusing on China's efforts to shape the global digital economy, infrastructure, and cybersecurity frameworks. The aim of the research is to analyze China's cyber diplomacy efforts through its Digital Silk Road and how these initiatives help in building geopolitical influence. The methodology involves qualitative analysis of primary and secondary data sources, including government reports, academic literature, and international case studies. Data analysis techniques include content analysis and comparative studies of China's digital infrastructure investments across various regions. Findings indicate that China’s DSR is not just about economic investments but also aims to establish a global technological dominance, shape global cybersecurity norms, and promote Chinese technological standards. Recommendations for countries engaging with the DSR include ensuring strong cybersecurity frameworks and aligning with international standards to avoid over-reliance on Chinese technologies. The study also suggests future implications for global governance, highlighting the need for balanced cooperation and competition in the digital domain. In conclusion, China's Digital Silk Road represents a critical tool in its cyber diplomacy strategy, influencing both digital economies and international relations.